Effect of row spacing and varieties on growth and yield of linseed (Linum usitatissimum L.): EFFECT OF ROW SPACING AND VARIETIES ON GROWTH AND YIELD OF LINSEED - D K PRAJAPATI; C K DESAI; J S DESAI; P B RABARI (Journal of Oilseeds Research, 2024)
A field experiment was conducted during rabi season of 2021-22 to study the effect of row spacing and varieties on growth and yield of linseed. There were nine treatment combinations comprising of three row spacings (22.5 cm, 30 cm and 45 cm) and three varieties (Neelam, T 397 and Pusa 3) were tested in a split plot design. Significantly the highest plant population at 30 DAS and at harvest as well as plant height at 30, 60 DAS and at harvest were recorded under the row spacing of 22.5 cm. Significantly the highest numbers of branches per plant, number of capsules per plant and test weight were observed under the row spacing of 45 cm. Linseed sown at narrow row spacing of 22.5 cm produced significantly the highest seed and stover yield. The maximum net realization and benefit cost ratio were recorded under the row spacing of 22.5 cm. Pusa 3 variety recorded significantly the highest plant height at 30, 60 DAS and at harvest. Significantly higher number of branches per plant, number of pods per plant, test weight and seed yield were recorded with Pusa 3 variety but it was remained at par with T 397 variety. The variety Pusa 3 recorded significantly the highest stover yield. The maximum net realization and benefit cost ratio were accured with the Pusa 3 variety.